Examen Especial a Inversiones en Bienes de Larga Duración del Gobierno Autónomo Descentralizado Municipal Intercultural de Saraguro, periodo 01 enero-31 diciembre 2022 - González Torres, Jessica Tatiana (2024)
The following work entitled: "Special Examination of Investments in Long-Lived Assets of the Municipal Intercultural Decentralized Autonomous Government of Saraguro, Period 01 January-31 December 2022"; was completed in order to meet the proposed objectives through the evaluation of internal control, the verification of legality, the veracity and ownership of long-term assets, through the practical implementation of the special examination, culminating in the preparation of a final report that summarizes the results. A methodology was used, based on the phases of the special examination, which included the creation of the work order, notification of the beginning of the special examination, the mark sheet and index, as well as the schedule and distribution of the time and work. In the next step, the plan was developed, which was divided into preliminary and specific planning, providing general and specific information regarding the institution.; In the execution phase, the respective work program was formulated with the necessary objectives and procedures, where the internal control was evaluated, which shows that the institution does not have a regulation related to the physical custody and security of long-lived assets; it has been determined that reconciliations of balances between warehouse and accounting have not been performed, the assets have not been written off, and no technical reports have been prepared for disposal. Additionally, it was verified that the institution has the necessary documentation to support acquisitions; however, there are assets that do not have the correct record of their useful life, which affects the computation of depreciation for long-lived assets, which adversely impacts the accuracy and integrity of asset management. Subsequently, a summary statement was made with the respective adjustment entries in order to determine the value corresponding to the account investments in long-lived assets, consecutively the respective analytical statement was prepared to establish the movement of the accounts that make up the component under examination, determining that the process is correctly applied according to the analysis of the general ledger. Additionally, the report was developed that refers to the findings of the examination as well as the conclusions and recommendations addressed to the principal officers responsible for managing, conserving, and controlling the assets. By taking corrective measures, corrective measures are taken to direct their operations and internal control, contributing to achieving institutional objectives.